2018
DOI: 10.1007/s10533-018-0449-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of flooding on aquatic ecosystem services

Abstract: Flooding is a major disturbance that impacts aquatic ecosystems and the ecosystem services that they provide. Predicted increases in global flood risk due to land use change and water cycle intensification will likely only increase the frequency and severity of these impacts. Extreme flooding events can cause loss of life and significant destruction to property and infrastructure, effects that are easily recognized and frequently reported in the media. However, flooding also has many other effects on people th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(96 citation statements)
references
References 165 publications
(206 reference statements)
0
96
0
Order By: Relevance
“…During the flood, we observed a significant depauperisation in the chrysophyte species composition compared to the previous data. Thus, recent studies demonstrated that the beginning of a flood was accompanied by species impoverishment in plankton communities, even if the silicon and nitrogen concentrations were sufficient for their development (Talbot et al 2018). We suggested that the concentrations of chemical components, including oxygen, silicon, nitrogen, and phosphorous could not limit the development of silica-scaled chrysophytes in studied area.…”
Section: Impact Of Floods On Silica-scaled Chrysophyte Diversitymentioning
confidence: 77%
See 1 more Smart Citation
“…During the flood, we observed a significant depauperisation in the chrysophyte species composition compared to the previous data. Thus, recent studies demonstrated that the beginning of a flood was accompanied by species impoverishment in plankton communities, even if the silicon and nitrogen concentrations were sufficient for their development (Talbot et al 2018). We suggested that the concentrations of chemical components, including oxygen, silicon, nitrogen, and phosphorous could not limit the development of silica-scaled chrysophytes in studied area.…”
Section: Impact Of Floods On Silica-scaled Chrysophyte Diversitymentioning
confidence: 77%
“…The flood pulse concept elaborated by Junk et al (1989) stated that a seasonal flood is useful for river ecosystems and could affect their biotic composition, nutrient transport, and sediment distribution. However, violent floods can be destructive for aquatic organisms (Talbot et al 2018).…”
Section: Impact Of Floods On Silica-scaled Chrysophyte Diversitymentioning
confidence: 99%
“…Then again, the destructive consequences of floods are well known, which causes loss of lives and properties (Talbot et al, 2018). Nevertheless, agricultural (oil palm) remains the backbone of the Malaysian economy and structural development.…”
Section: Background Of the Studymentioning
confidence: 99%
“…3). For example, high-frequency, low-intensity floods enhance many ecosystem services while low-frequency, high-intensity floods generate losses in ecosystem services (Talbot et al 2018). River restoration strategies for reducing pollution from extreme events can be improved by identifying features along drainage networks such as floodplains, wetlands, oxbow ponds, and reservoirs, which enhance hydrologic retention, and lengthen the distribution of hydrologic residence times (Wohl et al 2017;Wollheim et al 2018).…”
Section: Resilience Of Water Quality To Extreme Climate Eventsmentioning
confidence: 99%